Improved innovative product strategy assessment model in market research context - Braslina, Liga; Batraga, Anda; Skiltere, Daina; Legzdina, Aija; Braslins, Girts; Cildermane, Eva (University of Latvia, 2019)
In the innovation economy, companies more often face the need quickly and efficiently evaluate not only their existing product and service portfolios in the context of the industry’s potential, but also evaluate theoretical concepts of innovations. There are various systems for evaluating innovation concepts and already existing products and/or services for companies that are planning to expand their business in a new industry. The innovation economy is characterized by the convergence of innovations and the most demanded products on the market with continuous market upgrades. A company which wants to grow in a new industry faces an assessment challenge between already existing, demanded products and the choice of innovative concepts in the context of the company's most perspective growth. As market examples show, a successful company’s entry into a new industry can be related to both an innovative concept and an innovative business model of existing, demanded market products. The aim of the study is to analyse the appropriateness of the existing assessment systems of innovations concepts and market bestselling products from the perspective of an enterprise, considering an expansion into new industry. The theoretical benefit of the study is to highlight a new, complementary model in the assessment of the company's growth strategy in the context of developing new industries and markets. The practical contribution of the study is an improved combined industry and company assessment model. Proposed model is company growth perspective assessment tool in the context of new products, either it is completely new to market or new to company, but already known in the market.
Keywords: NPD evaluation model; industry attractiveness model; company growth analyses; market research; Research Subject Categories::SOCIAL SCIENCES::Business and economics